Association of Mineral Bone Disorder With Decline in Residual Kidney Function in Incident Hemodialysis Patients. (30th October 2019) - Lee, Yu‐Ji; Okuda, Yusuke; Sy, John; Obi, Yoshitsugu; Kang, Duk‐Hee; Nguyen, Steven; Hsiung, Jui Ting; Park, Christina; Rhee, Connie M; Kovesdy, Csaba P; Streja, Elani; Kalantar‐Zadeh, Kamyar
ABSTRACT: Abnormalities of mineral bone disorder (MBD) parameters have been suggested to be associated with poor renal outcome in predialysis patients. However, the impact of those parameters on decline in residual kidney function (RKF) is uncertain among incident hemodialysis (HD) patients. We performed a retrospective cohort study in 13, 772 patients who initiated conventional HD during 2007 to 2011 and survived 6 months of dialysis. We examined the association of baseline serum phosphorus, calcium, intact parathyroid hormone (PTH), and alkaline phosphatase (ALP) with a decline in RKF. Decline in RKF was assessed by estimated slope of renal urea clearance (KRU) over 6 months from HD initiation. Our cohort had a mean ± SD age of 62 ± 15 years; 64% were men, 57% were white, 65% had diabetes, and 51% had hypertension. The median (interquartile range [IQR]) baseline KRU level was 3.4 (2.0, 5.2) mL/min/1.73 m 2 . The median (IQR) estimated 6‐month KRU slope was −1.47 (−2.24, −0.63) mL/min/1.73 m 2 per 6 months. In linear regression models, higher phosphorus categories were associated with a steeper 6‐month KRU slope compared with the reference category (phosphorus 4.0 to <4.5 mg/dL). Lower calcium and higher intact PTH and ALP categories were also associated with a steeper 6‐month KRU slope compared with their respective reference groups (calcium 9.2 to <9.5 mg/dL; intact PTH 150 to <250 pg/mL; ALP <60 U/L). The increased number of parameter abnormalities had an additive effect on decline in RKF. Abnormalities of MBD parameters including higher phosphorus, intact PTH, ALP and lower calcium levels were independently associated with decline in RKF in incident HD patients. © 2019 American Society for Bone and Mineral Research. © 2019 American Society for Bone and Mineral Research.